Prognostic value of pretreatment inflammatory biomarkers in advanced lung adenocarcinoma patients receiving first-line pemetrexed/platinum doublet - Yanjuan Xiong; Ning Zhao; Yu Zheng; Jian Wang; Feng Wei; Xiubao Ren (Tumor Biology, 2017)
Inflammation is a new hallmark feature of cancer initiation and progression. We aimed to investigate the association between inflammatory response biomarkers and progression-free survival and overall survival in advanced lung adenocarcinoma patients treated with first-line pemetrexed and platinum doublet chemotherapy. Patients hospitalized between April 2012 and March 2015 were enrolled and eliminated according to the inclusion and exclusion criteria. The pretreatment neutrophil-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, derived neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio were calculated. Besides the well-established clinical prognostic factors, the prognostic values of the four markers were evaluated by the Kaplan–Meier method and Cox’s proportional hazards regression model. A total of 78 patients were enrolled in this study. Elevated neutrophil-to-lymphocyte ratio and derived neutrophil-to-lymphocyte ratio were correlated with poor treatment response ( p = 0.014, 0.012, respectively). A high pretreatment neutrophil-to-lymphocyte ratio, derived neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio, as well as low lymphocyte-to-monocyte ratio, were associated with worse progression-free survival and overall survival. Multivariate analysis revealed that high neutrophil-to-lymphocyte ratio (hazard ratio = 2.056; 95% confidence interval, 1.281–3.299; p = 0.003) and ≥3 metastasis organs (hazard ratio = 1.989; 95% confidence interval, 1.069–3.702; p  = 0.030) were independent prognostic factors for progression-free survival. Meanwhile, high neutrophil-to-lymphocyte ratio (hazard ratio = 5.540; 95% confidence interval, 2.974–10.321; p < 0.001) and habitual smoking (hazard ratio = 2.806; 95% confidence interval, 1.509–5.221; p = 0.001) were independent prognostic factors for overall survival. In conclusion, Pretreatment neutrophil-to-lymphocyte ratio was an independent prognostic factor for advanced lung adenocarcinoma patients treated with first-line pemetrexed/platinum doublet chemotherapy. Elevated pretreatment derived neutrophil-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio might be potential biomarkers for poorer responses to chemotherapy. To verify these findings, larger well-designed prospective studies are needed.